(3EQTGO GdSGFd Edi CUhd GdeSGFds - (3CHh GdYHGS TgGH GdOjf CMeO Hf QLH GHf GdeLOis; (3CHh YHO GdQMef LeGd GdOjf YHO Gddg Hf Ndjd Hf jhSa GdeGQOjfjs
(3ChdgG (B:s
(3aEf GdhSGFd JTQa dTQa ebGUOgG hcGf GdYde GdeJcad HPdc Yde GdejbGJ hGf TjNfG GdeGQOjfi bO LeY ebOeI ai gPG Gdaf s
(3BNQgG (B:s
(3ESJNQL GdYdGeJjf GdChdi hGdKGfjI HGdWQjb GdKGdKI ai HGH GdLgGJ hVY EMOi QLdjg Ydi GdYdGeI GdJi ai LgI GdeTQb , (B( (3hYdi (B) (3GdeZQH HYdGeI CNQi GLeY Hjf gPG GdJbGWY hGdfbWI GdJi hVYJ YdjgG s
(3HgG fXGe GdJYbjHIs
(3NGdjI ef GdCTcGd hGdQShes
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B270s
Keywords: (3Gdadcs